2019
DOI: 10.26444/monz/102392
|View full text |Cite
|
Sign up to set email alerts
|

Perception of European nurses of culturally-appropriate health care – a cross-sectional study

Abstract: Introduction and objective. Increased migration within Europe is leading to rapid population changes in every country. Nurses increasingly care for patients with whom they do not share a common culture or language. The aim of this study is to ascertain nurses' perceptions of difficulties in providing culturally appropriate care. Materials and method. Survey questions derived from the literature were translated from Slovak into 5 languages, then distributed to nurses in 25 European States. The survey sample con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…From the perspective of patients, healthcare professionals, and healthcare systems, there are potentially many approaches that could help improve adherence. We agree with the authors' opinions [23][24][25][26][27][28] that one of the most effective and important ways is providing consistent patient education. Other alternatives are to use motivational interviewing [29] or a mobile phone application [5].…”
Section: Health Problems Of Civilizationsupporting
confidence: 73%
“…From the perspective of patients, healthcare professionals, and healthcare systems, there are potentially many approaches that could help improve adherence. We agree with the authors' opinions [23][24][25][26][27][28] that one of the most effective and important ways is providing consistent patient education. Other alternatives are to use motivational interviewing [29] or a mobile phone application [5].…”
Section: Health Problems Of Civilizationsupporting
confidence: 73%
“…Another significant influence on cultural competence reported in the literature was the ability to communicate in at least one foreign language (Repo et al, 2017). Červený, Siaki, McGee, and Kilíková (2019) surveyed nurses from 25 countries in the European Union ( n = 1,264). One of the greatest challenges to providing culturally congruent care identified in their study was language barriers (44.9%).…”
Section: Discussionmentioning
confidence: 99%
“…As the number of people with different cultural backgrounds in Austria has increased, the cultural diversity in the Austrian healthcare system has also increased. Despite the demonstrated importance of exhibiting cultural competence in terms of improving patient outcomes and nursing competencies, nurses working in the European countries of Germany, Czech Republic, Hungary, Slovakia, and Poland do not generally perceive themselves as culturally competent [ 10 ]. Most of the nurses (70.6%) indicated that they faced challenges while providing nursing care for patients with different cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%